How does procreation relates to a Muslim woman? - Nur Aisyah Gersali. (2012)
The anatomy is destiny. Therein lies the idea that women are destined to procreate due to biological determinism. This present study however, seeks to understand the relationship between procreation and Islam given the higher fertility rates of Muslims in many parts of the world in comparison to other religions. It seeks to understand if the Islamic viewpoint where the anatomy really is destiny had encouraged procreation amongst Muslim women in Singapore. On top of that, this study also seeks to see how these women internalize the notion of procreation alongside their other socially defined womanly roles as Mothers and Wives.